The optimal level of the inflation target: A selective review of the literature and outstanding issues - Oleksiy Kryvtsov; Rhys R. Mendes (Bank of Canada, 2015)
Bank of Canada research done prior to the most recent renewal of the inflation-control agreement in 2011 concluded that the benefits associated with a target below 2 per cent were insufficient to justify the increased risk of being constrained by the zero lower bound (ZLB) on nominal interest rates. International experience and analysis since the 2011 renewal has reinforced the importance of the ZLB. Despite the deployment of unconventional monetary policy measures by many central banks, the ZLB has proven to be a more severe and persistent obstacle to the achievement of policy goals than expected. At the same time, analysis by the Bank and others has found that interest rates are likely to be lower on average in the future than they were during the first two decades of inflation targeting. As a consequence, the probability of being constrained by the ZLB is likely higher. Together, these factors suggest that a target above 2 per cent should be considered. This paper provides an overview of the current state of knowledge and key outstanding issues regarding the costs and benefits of a higher inflation target. – – D'après les recherches effectuées à la Banque du Canada avant le dernier renouvellement de l'entente sur la maîtrise de l'inflation en 2011, les avantages découlant d'une cible inférieure à 2 % ne justifiaient pas le risque accru d'être contraints par la borne limitant à zéro les taux d'intérêt nominaux (la « borne du zéro »). L'expérience acquise et les analyses menées à l'échelle internationale depuis le renouvellement de 2011 ont confirmé l'importance de la borne du zéro. Bon nombre de banques centrales ont mis en place des mesures de politique monétaire non traditionnelles, mais la borne du zéro s'est révélée un obstacle à la réalisation des objectifs de politique monétaire plus grave et plus persistant que prévu. En outre, selon les analyses conduites à la Banque et ailleurs, les taux d'intérêt devraient à l'avenir être inférieurs en moyenne au niveau qu'ils affichaient pendant les vingt premières années du ciblage de l'inflation. Par conséquent, la probabilité d'être contraints par la borne du zéro est sans doute plus élevée qu'anticipé. Compte tenu de tous ces facteurs, une cible supérieure à 2 % devrait être considérée. Les auteurs présentent une vue d'ensemble de l'état actuel des connaissances ainsi que les principales questions en suspens entourant les avantages et les inconvénients d'une cible d'inflation supérieure.
Keywords: E; E5; E52; E58; 330; Monetary policy framework; Inflation targets; Inflation; costs and benefits; Cadre de la politique monétaire; Cibles d'inflation; Inflation; coûts et avantages